Copper-catalyzed ARGET ATRP of styrene from ethyl α-haloisobutyrate in EtOAc/EtOH, using ascorbic acid/Na2CO3 as reducing system. (15th August 2021) - Borsari, Marco; Braidi, Niccolò; Buffagni, Mirko; Ghelfi, Franco; Parenti, Francesca; Porcelli, Nicola; Serafini, Gaia; Isse, Abdirisak Ahmed; Bonifaci, Luisa; Cavalca, Gianfranco; Longo, Aldo; Morandini, Ida; et al.
Graphical abstract: Highlights: "Green" and inexpensive ARGET ATRP for the synthesis of polystyrene. Chlorine and bromine ATRP systems. Solvent mixture composed of ethyl acetate and ethanol, even in the presence of modest amounts of H2 O. High yields and low dispersities with low amounts of copper catalyst. Abstract: Atom transfer radical polymerization (ATRP) is one of the most powerful techniques to synthesize precisely tailored polymers and macrostructures. Activators regenerated by electron transfer (ARGET) ATRP was developed as a "green" strategy to decrease the load of the metal catalyst. However, ARGET ATRP usually uses not-so-green reducing agents (e.g. Sn 2+ ) or expensive and industrially impractical procedures. For these reasons, we report an ARGET ATRP of styrene with various carbonates as reducing agents, both alone and paired with ascorbic acid (AA), using monofunctional initiators and Cl or Br as exchanging atoms. The solvent mixture is composed of the green combination of EtOAc and EtOH, even in the presence of modest amounts of H2 O. Cyclic voltammetry was used to evaluate the effect of H2 O on the catalyst, as well as the absence of AA. The system returned high yields and low dispersities with low amounts of catalyst (~60 ppm) and moderate reaction times. Excellent results were obtained only with the Cl-ATRP system. NMR spectroscopy and kinetic analyses proved the livingness of the final polymer chains.